Nghiên cứu khả năng nhả chậm chất khoáng N-P-K trong phân hữu cơ khoáng trên nền than bùn. Phần I – Phân khoáng Đơn - Hương, Bùi Thanh; Vinh, Nguyễn Quang; Lộc, Lưu Cẩm (Vietnam Journal of Chemistry, 2014)
The adsorptions of nutrient N, P, K on the Ca Mau peat and Tay Ninh peat have been studied. The Ca Mau peat absorption capacities of nutrient cations (NH4+ and K+) are higher than Tay Ninh peat, but the adsorption of phosphate anions is less. The releases of N, P, and K nutrient from mineral organic fertilizers contented single mineral nutrition with different compositions have been investigated. The single mineral fertilizers composted with 8% mineral nutrient have higher slow-release effect. The colloidal humic system plays main part in phosphorus slow-release.